(3GdMeGjI GdbGfhfjI deSJNOej GdGJUGdGJ hGdEfJQfJ (B/s - (3GdTjN, CMeO eMeO YHO GdYRjRs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2019)
(3jJfGhd cJGH (B((3GdMeGjI GdbGfhfjI deSJNOej GdGJUGdGJ hGdEfJQfJ(B) (3GdPj bGe HJCdjag (B( (3CMeO eMeO YHO GdYRjR(B) (3aj MhGdj (B(381) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdGJUGdGJ(B) (3eJVefG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdJegjOj (B: (3eaGgje CSGSjI aj eLGd GdGJUGdGJ hGdEfJQfJ hjfbSe Edi aUdjf, GdHGH GdChd (B: (3Mbhb GdeSJNOe hGdWHjYI GdbGfhfjI dYbhO NOeGJ GdGJUGdGJ hjfbSe Edi aUdjf, GdHGH GdKGfj (B: (3GdMeGjI GdbGfhfjI aj YbhO GdGSJgdGc hYbhO NOeGJ GdGJUGd hjfbSe Edi CQHYI aUhd, GdHGH GdKGdK (B: (3GdMeGjI GdbGfhfjI dMbhb eSJNOej GdGJUGdGJ hGdEfJQfJ hjfbSe Edi aUdjf, jJVef eQGLY HHdjhLQGajI(B.s
(3HHdjhLQGajI (B: (3UaMI (B345-377.s
Keywords: (3GdGJUGdGJs -- (3bhGfjf hJTQjYGJs; (3GdEfJQfJs -- (3bhGfjf hJTQjYGJs; (3THcGJ GdGJUGdGJ GdSdcjI hGddGSdcjIs -- (3bhGfjf hJTQjYGJs; (3GdeSFhdjI GdeOfjIs -- (3bhGfjf hJTQjYGJs; (3MeGjI GdeSJgdcs -- (3bhGfjf hJTQjYGJs; (3YbO NOeGJ GdGJUGdGJs; (3NOeGJ GdEfJQfJs; (3bGfhf GdGJUGdGJs